Emerging Role of Gasotransmitters in Renal Transplantation. Issue 12 (30th October 2013) - Snijder, P. M.; van den Berg, E.; Whiteman, M.; Bakker, S. J. L.; Leuvenink, H. G. D.; van Goor, H.
Abstract Once patients with kidney disease progress to end‐stage renal failure, transplantation is the preferred option of treatment resulting in improved quality of life and reduced mortality compared to dialysis. Although 1‐year survival has improved considerably, graft and patient survival in the long term have not been concurrent, and therefore new tools to improve long‐term graft and patient survival are warranted. Over the past decades, the gasotransmitters nitric oxide (NO), carbon monoxide (CO) and hydrogen sulfide (H2S) have emerged as potent cytoprotective mediators in various diseases. All three gasotransmitters are endogenously produced messenger molecules that possess vasodilatory, anti‐apoptotic, anti‐inflammatory and anti‐oxidant properties by influencing an array of intracellular signaling processes. Although many regulatory functions of gasotransmitters have overlapping actions, differences have also been reported. In addition, crosstalk between NO, CO and H2S results in synergistic regulatory effects. Endogenous and exogenous manipulation of gasotransmitter levels modulates several processes involved in renal transplantation. This review focuses on mechanisms of gas‐mediated cytoprotection and complex interactions between gasotransmitters in renal transplantation.